Correlation of neonatal birth weight with other anthropometric measurements - A cross-sectional study - Chaudhuri, Saugata; Hota, Moumita (Indian Journal of Child Health, 2018)
Background: About 60–80% of neonatal deaths are due to low birth weight (LBW <2500 g) in developing countries. Objectives: The objectives of this study was to identify a suitable anthropometric surrogate and to identify LBW babies in the resource limited settings like rural areas where 80–90% deliveries take place to screen the LBW babies. Materials and Methods: A total of 1000 newborns were studied by random sampling method. BW and other anthropometric measurements were taken within 24 h of birth. Results: All key anthropometric parameters were significantly correlated to each other. The maximum correlation was with midthigh circumference (MTC) (R2=0.683), followed by foot length (FL), midarm circumference (MAC), and head circumference (HC), followed by length and least with the chest circumference (CC). Conclusion: Although MTC is the most sensitive parameter in this study, additional use of other parameters such as FL, HC, MAC, and length and CC significantly improves the predictive value of identifying LBW babies.